Aflatoxin B1 Quantification from Fish Feeds and Fishery Products in Kisumu and Uasin Gishu Counties, Kenya - Chelimo, S. J.; Osano, O.; Isaboke, J.; Menya, D. (Africa Environmental Review Journal, 2021)
Mycotoxins are toxic compounds produced by fungi as secondary metabolites. Their level of occurrence has gained global concern, especially in the aquaculture industry, because mycotoxins have shown to be persistent in fish flesh, causing a severe threat to animal welfare and human health. Communities should be aware of the dangers of Aflatoxin so that such knowledge will enable them to handle fish feeds appropriately. This study aimed at establishing contributing factors leading to mycotoxin contamination among farmers and fish feed traders on their effects and possible management strategies. A questionnaire and an observation checklist were used to collect data. A Cross-sectional exploratory study was employed; both qualitative and quantitative data were collected. The Snowball technique was used to identify the respondents. The data were analyzed using Statistical Package for Social Sciences (SPSS) version 24, Binary logistic regression was used to determine associations, and descriptive statistics were used to analyze data. Sixty-two respondents were interviewed; results indicate that more women farmers, 34 (54.8%), participated in the interview than men, 28 (45.2%). Most of the respondents, 53.2%, attained secondary 24.2%, and 11.3% tertiary education in both counties. Among the respondents who have heard of mycotoxins, a quarter (OR: 1.003) of them have heard of Aflatoxins only. Maize 49.7% with a mean of (±14.2) was the primary fish feed ingredient. Out of the 62 samples, 19.4% (±1.33; SD 0.592) were contaminated with AFB1, with the majority of the contaminated feeds 66.7% (±0.25; SD 0.44) were from Kisumu County. Traders were 0.006 times likely to have better knowledge of Aflatoxin than farmers. The findings have shown that education holds a positive and significant correlation with the level of knowledge and occurrence of those who attained secondary (OR 1.078: CI 0.736-1.580) and college (OR 1.050: CI 0.594-1.856). Some of the storage practices were found to influence the exposure of the feeds to the growth of fungi and mycotoxin contamination. Hence, there is a need for more sensitization and training targeting farmers and traders. Additionally, there is a need for a heightened surveillance program to monitor local ingredients, finished feeds, and storage processes.